Comment on: Predicting In‐Hospital Mortality in COVID‐19 Older Patients with Specifically Developed Scores. Issue 4 (22nd January 2021) - Odille, Geoffrey; Girard, Noémie; Sanchez, Stephane; Lelarge, Sarah; Mignot, Alexandre; Putot, Sophie; Larosa, Fabrice; Vovelle, Jeremie; Nuss, Valentine; Da Silva, Sofia; Barben, Jeremy; Manckoundia, Patrick; et al.
Abstract : See the Reply by De Matteis et al .